TERAPI SEFT (SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE) TERHADAP TINGKAT KECEMASAN PADA PASIEN PRE OPERASI - Imam Abdurrohman; Lukman Nulhakim; Arifin Hidayat (Bajang Institute, 2023)
Pre-operative is an action before surgery is carried out on the operating table, which can cause psychological problems, namely anxiety. Efforts to overcome anxiety that occurs in preoperative patients can be done with SEFT therapy. Spiritual Emotional Freedom Technique (SEFT) is a treatment technique that combines the body's energy system and spiritual techniques through light tapping at 18 points along the body's 12 energy pathways. Quantitative quasi-experimental research design, pretest-posttest method with control group design. The research population of preoperative patients at Taman Husada Bontang Hospital, the number of respondents was 36 patients, 18 respondents each in the control and intervention groups. Statistical test using paired t-test. The research results showed that the average anxiety score before SEFT therapy was 15.39 (moderate anxiety), while the average anxiety score after SEFT therapy was 10.89 (mild anxiety). Statistical test analysis used the paired t test with a result of 0.012 (p < α 0.05). The research results showed the effect of SEFT therapy on the patient's preoperative anxiety level.